[18F]-T807 tauopathy PET imaging in chronic traumatic encephalopathy [v1; ref status: indexed, http://f1000r.es/4fb] - Sam Gandy; Steven T. DeKosky (F1000Research, 2014)
A new molecular ligand for positron emission tomography (PET) of the human brain, [18F]-T807, is under investigation for the antemortem detection of pathological neurofibrillary aggregates, which are evidence of neurofibrillary tangle (NFT) diseases, also known as tauopathies. Repetitive mild traumatic brain injuries in athletes and battlefield veterans are associated with one such tauopathy, known as chronic traumatic encephalopathy (CTE). In a recent case report, a former NFL player with clinically probable CTE and a concurrent Progressive Supranuclear Palsy (PSP) –like syndrome was studied using [18F]-T807. The interpretation of this player’s [18F]-T807 PET imaging was complicated by the overlap of tracer uptake in brain regions involved in CTE and PSP with regions associated with either nonspecific [18F]-T807 ligand binding or “aging-associated” binding of [18F]-T807 to authentic tauopathy known to be associated with aging and disease severity (i.e., NFT in the mesial temporal lobe). The implications of these data for the utility of [18F]-T807 in the pre-mortem detection of CTE are summarized.